Indonesia's G20 Leadership: Navigating National Ambitions on the Global Stage - Ujang Komarudin; Syafiuddin Fadlillah (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2024)
In today's interconnected world, nations confront complex economic challenges. The G20 serves as a crucial forum for coordinated action, with member countries taking turns in the annual presidency. Indonesia's stewardship in 2022 was marked by a concerted focus on global economic recovery, especially in the wake of the momentum of COVID-19, and the demonstration of its leadership prowess on the international stage. This study employs qualitative research methods and national interest theory to delve into Indonesia's strategic priorities during its historic first G20 presidency in 2022. Through a meticulous analysis of Indonesia's initiatives, it becomes evident that the presidency not only advanced the interests of the G20 as a whole but also brought significant benefits to Indonesia, the ASEAN region, and developing countries worldwide. This examination underscores Indonesia's adept maneuvering and strategic engagement within the broader global economic landscape.